DEVELOPMENT OF AN AUTOMATED FLOW RATE ESTIMATION METHOD - EMALISA BINTI KAMSANI, EMALISA (Universiti Teknologi Petronas, 2012)
In this project, a flow rate estimation mettrod will be developed using the MATL^ab algorithm. This method can be use to estimate a volume flow rate of leaking fluid to the environment. On 2010, there was oil spill in BH fbepwater Horizon. Many assumptions have been made about the total amount of leaking. Few methods have been devel@ but none of them can be consider as accurate. At Ore en4 diffenent psths has becn omtc out with different conclusion. fire experiment will be basod on the Pafiical ltnage Velocimetry ef$ mahod. An experiment will be set up for this shrdy. A Kinect 3D camera was used to rcoord &c flow rate analogt. From the video, fen, sas of imagss was takcn $e @l]4fr& Thc analysis was complaed usingthe Image ProcessingTml. Bas€d on the analysis, the velocity with highest frroquency rocordod is 0.70t m/s and the volume flow rate is 3.475 crnYs. While tte volumc flow ratc rcqH during experiment is 3.333 cm3/s. Therefore the ditrerenoe p€rccntsgc is4269L.